IMPLEMENTASI SAPTA PESONA DALAM UPAYA MEMBANGUN CITRA DESTINASI WISATA PANTAI AIR BANGIS DI KABUPATEN PASAMAN BARAT - Fyona Hadisty; Sandra Dewi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research was motivated by the unmanaged implementation of Sapta Pesona in the Air Bangis beach tourist destination, which resulted in a lack of order in the parking area because it took up the road and disturbed other motorists. Apart from that, there are still very few traders selling souvenirs or typical food at the Air Bangis beach destination. This type of research is descriptive qualitative research namely the data collected is in the form of words, pictures, not numbers, placing greater emphasis on observing phenomena and digging deeper into the meaning behind the Air Bangis beach destination. The data collection technique used in this research is through interviews by going directly to the location of the Air Bangis beach destination and documentation to obtain written data related to this thesis. The implementation of Sapta Pesona among tourist destination managers is a delusion towards sustainable tourist destinations. Based on the results of the research conducted, it can be concluded that the implementation of Sapta Pesona in the tourist destination of Air Bangis Beach does not yet understand Sapta Pesona tourism, which has an impact on tourism managers not being optimal and also the public still not understanding the importance of Sapta Pesona elements as a barometer of tourism around Air Bangis Beach